The entrepreneurial mindset and self-employment intention of high school learners: The moderating role of family business ownership - Chilenga, Ntharika; Dhliwayo, Shepherd; Chebo, Abdella K. (Frontiers in Education, 2022)
Entrepreneurship, through successful business venturing, plays a pivotal role in a nation’s endeavor to create jobs and boost the economy. The Global Entrepreneurship Monitor (GEM) reports state that South Africa’s early stage total entrepreneurial activity (TEA) is lower than most countries that are at comparable levels of development. Therefore, the entrepreneurial mindset of high school learners and its influence on self-employment intention were assessed in this study. Also, the moderating effect of family business ownership on the relationship was measured. The data collected from 320 learners in randomly selected 10 high schools in Gauteng were analyzed using hierarchical regression analysis. The study finds that the level of an entrepreneurial mindset is above average, which provides the potential for a higher total entrepreneurial activity (TEA) in the future. Both entrepreneurial skills and entrepreneurial traits significantly influence self-employment intention, while learners’ family business background moderates the relationship. The study establishes the entrepreneurial mindset level of high school students in a country with one of the lowest TEA in the world, South Africa, where (possibly) the latest entrepreneurial mindset measure, the Entrepreneurial Mindset Profile (EMP) instrument is used. Also, it’s unique in testing the role of family business background in intensifying the entrepreneurial mindset toward self-employment intention. Therefore, the Department of Basic Education should aim to tap into the existing desire in high school learners and develop a curriculum that integrates theoretical and experiential learning. It is expected that this intervention will improve the future TEA of the country.